MORPHOLOGICAL PATTERNS OF CARDIOVASCULAR TERMINOLOGY: A COMPREHENSIVE ANALYSIS OF AFFIXATION AND BLENDING PROCESSES - Linnikova, Viktoriia; Surodeikina, Tetiana (Видавництво «Scentia», 2023)
This article explores the dynamic landscape of medical language, particularly within the cardio domain, influenced by technological advancements, scientific breakthroughs, and evolving patient demands. Rooted in the fundamental concept of morphology, which examines the structure and formation of words, the study delves into the morphological patterns shaping the terminology in cardiovascular medicine. The study focuses on morphological patterns, specifically affixation and blending, which contribute significantly to the creation of medical terms.
Keywords: morphology; cardiovascular; affixation; blending; terminology